2013
DOI: 10.4067/s0717-95022013000400024
|View full text |Cite
|
Sign up to set email alerts
|

Sex Determination from Occipital Condylar Measurements by Baudoin Index in Forensic Purposes

Abstract: SUMMARY:In human identification for forensic purposes the sex is one of the most important and first features to be assessed in each case. Baudoin condylar index is a sex determination method based on measurements of length and width of the occipital condyle. The aim of this research was to apply the Baudoin condylar index for sex determination, and evaluate its reliability. The sample was composed of 100 Brazilian human skulls, 50 male and 50 female from São Gonçalo cemetery, City of Cuiabá, Brazil. The measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 16 publications
(29 reference statements)
1
8
1
2
Order By: Relevance
“…These finding were in corroboration with the study done in Brazil by Oliviera et al [8] (Table 6) The mean antero-posterior diameter of right occipital condyle of male skulls in the present study (22.95 ± 2.98) was lower than the Brazilian male skulls (26.74 ± 2.96) [8] while that of female skulls (21.07 ± 3.09) in the present study was also lower than the Brazilian population (25.45 ± 3.21) [8]. Similarly the mean antero-posterior diameter of left occipital condyle of male skulls in the present study (22.34 ± 3.35) was lower than the Brazilian skulls (26.85 ± 2.97) [8] and that of female skulls in the present study (22.25 ± 2.65) was also lower than the Brazilian population (24.65 ± 3.23) [8]. (Table 6) From the results obtained in our study it was observed that the mean transverse diameter of right occipital condyles of male skulls (11.36 ± 1.77 mm) was slightly lower than female skulls (11.43 ± 1.67 mm) but the difference was not statistically significant.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…These finding were in corroboration with the study done in Brazil by Oliviera et al [8] (Table 6) The mean antero-posterior diameter of right occipital condyle of male skulls in the present study (22.95 ± 2.98) was lower than the Brazilian male skulls (26.74 ± 2.96) [8] while that of female skulls (21.07 ± 3.09) in the present study was also lower than the Brazilian population (25.45 ± 3.21) [8]. Similarly the mean antero-posterior diameter of left occipital condyle of male skulls in the present study (22.34 ± 3.35) was lower than the Brazilian skulls (26.85 ± 2.97) [8] and that of female skulls in the present study (22.25 ± 2.65) was also lower than the Brazilian population (24.65 ± 3.23) [8]. (Table 6) From the results obtained in our study it was observed that the mean transverse diameter of right occipital condyles of male skulls (11.36 ± 1.77 mm) was slightly lower than female skulls (11.43 ± 1.67 mm) but the difference was not statistically significant.…”
Section: Resultssupporting
confidence: 83%
“…Though the measurements in male skulls were slightly higher than the female skulls the difference was not statistically significant (Table 4). In contrast to the present study, a study done in Brazil by Oliveira et al shows that the average transverse diameter of right occipital condyle in male & female skulls was 13.51 ± 1.38 mm & 12.68 ± 1.56 mm respectively while the transverse diameter of the left occipital condyles in male & female skulls was 13.79 ± 1.39 mm & 12.71 ± 1.75 mm respectively and the difference was statistically significant [8]. (Table 7) Different studies have quoted different facts and figures which have led to spectrum of findings.…”
Section: Resultscontrasting
confidence: 53%
See 1 more Smart Citation
“…[ [26] for Indians, Yu et al (2015), [14] for Chinese [22.75±2.90mm], Other researchers have also reported varying mean length of the OC of 13.59mm (Oliver, 1975), [27] , 22.9mm; right range of 15-27mm and left range of 15-29mm for Germans (Lang and Hornung, 1993), [23] 21 mm; range 18-24mm for Americans (Wen et al, 1997). [17] Kavithaet al (2013), [28] reported 21.97mm and 22.34mm for the right and left respectively while Salujaet al (2016), [16] reported mean values of 22.75±2.90mm for Indians.…”
Section: Resultsmentioning
confidence: 99%
“…[9] Name & Address of Corresponding Author Aigbogun (Jr) [8,13,14] with higher values reported for the Asians (Bozbugaet al, 1999; Yu et al, 2015; Salujaet al, 2016), [14][15][16] and lower values for the Caucasians and Australians (Wen et al 1997;Bazyatet al, 2014), [17,18] while for Africans the values fall between values of Asians and Caucasians (Salihet al, 2014; Agnihotriet al, 2014). [19,20] Only a few studies have reported morphometric values for the basilar process (clivus), with dimensions ranging from 24mm to 27mm (Oliviera, 1975; Wescott and Moore-Jansen, 2001), [21,22] and higher values for whites when compared to blacks (Wescott and Moore-Jansen, 2001). [22] Le et al, 2011; [13] Bozbugaet al, 1999; [14,15] Yu et al, 2015 Lang and Hornung, 1993; [23] have suggested that the inconsistencies in the morphometric values of the OC in different population could be attributed to differences in data acquisition, methodology and genetic endowment.…”
Section: Introductionmentioning
confidence: 99%